2004
DOI: 10.1104/pp.104.046169
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling the Effects of Abscisic Acid on Plant Growth and Water Relations. Analysis of sto1/nced3, an Abscisic Acid-Deficient but Salt Stress-Tolerant Mutant in Arabidopsis

Abstract: We have identified a T-DNA insertion mutation of Arabidopsis (ecotype C24), named sto1 (salt tolerant), that results in enhanced germination on both ionic (NaCl) and nonionic (sorbitol) hyperosmotic media. sto1 plants were more tolerant in vitro than wild type to Na 1 and K 1 both for germination and subsequent growth but were hypersensitive to Li 1 . Postgermination growth of the sto1 plants on sorbitol was not improved. Analysis of the amino acid sequence revealed that STO1 encodes a 9-cis-epoxicarotenoid di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 50 publications
6
112
0
6
Order By: Relevance
“…The RT-PCR product was then subcloned into pGEM-T Easy Vector (Promega) and sequenced. The HOS10 was released from the resulting clone 10-133 and cloned into binary vector 99-1 between SacI and XbaI sites, resulting in an expression cassette of HOS10 under the control of the cauliflower mosaic virus 35 S promoter. The construct was introduced into hos10-1 mutant plants through an A. tumefaciens-mediated (strain GV3101) T-DNA transformation.…”
Section: Aba Measurement and Real-time Pcr Analysis Of Nced3 Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RT-PCR product was then subcloned into pGEM-T Easy Vector (Promega) and sequenced. The HOS10 was released from the resulting clone 10-133 and cloned into binary vector 99-1 between SacI and XbaI sites, resulting in an expression cassette of HOS10 under the control of the cauliflower mosaic virus 35 S promoter. The construct was introduced into hos10-1 mutant plants through an A. tumefaciens-mediated (strain GV3101) T-DNA transformation.…”
Section: Aba Measurement and Real-time Pcr Analysis Of Nced3 Expressionmentioning
confidence: 99%
“…The HOS10 cDNA was cloned by RT-PCR using RNA prepared from wild-type plants. We conducted a complementation test by constitutive expression of HOS10 cDNA under the control of the cauliflower mosaic virus 35 S promoter. Twenty of 29 hos10-1 plants transformed with the wild-type HOS10 cDNA cassette exhibited wild-type phenotypes in the T 2 generation (Fig.…”
Section: Identification Of the Hos10 Genementioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the spatial distribution of carotenoid precursors and expression of ABA biosynthesis genes, including NCED itself, in a seed affect the contribution of each NCED to ABA biosynthesis. Among the five NCED genes in Arabidopsis, expression of NCED3 is induced by drought stress in plants (Iuchi et al, 2001;Ruggiero et al, 2004). In this study, we found that expression of NCED2, NCED5, and NCED9 was up-regulated by high temperature in after-ripened seeds under continuous illumination.…”
Section: Regulation Of Aba Biosynthesis By High Temperature In Seedsmentioning
confidence: 52%
“…Each member of the NCED family plays a unique regulatory role in specific environmental responses and developmental processes. Expression of the NCED3 gene is induced by drought stress, and it plays a major role in ABA synthesis in response to the stress (Iuchi et al, 2001;Ruggiero et al, 2004). NCED6 expression is regulated in a photoreversible manner via phytochrome in seeds, and it plays a role in far-red light-induced suppression of seed germination .…”
mentioning
confidence: 99%